Hemoglobinopathy Awareness Among Middle and High School Students In Karataş, Türkiye - Nazlıcan, Ersin; Akbaba, Muhsin (Scientific Reports in Medicine, 2024)
Objective:Hemoglobinopathies are complex and inherited genetic disorders with no definitive cure; however, preventive measures such as genetic counseling and premarital screening may dramatically reduce their prevalence. Therefore, having sufficient information about the mentioned preventive measures is crucial.Methods:All students attending middle and high schools were included without a sample selection. A survey form was administered to students in order to evaluate their knowledge level and attitudes regarding hemoglobinopathies. The results were evaluated using Chi-square and logistic regression analysis with 95% confidence interval (CI).Results:The total number of students agreeing to participate in the study was 877. The mean age of the participants was 14.8 ± 1.5 years; 50.5% of them were male.Of the participating students, 40.3% were previously informed about hemoglobinopathies.The lowest correct response rate among questions in terms of students’ knowledge about hemoglobinopathies was observed in the question that asked the transmission route of the disorders with 13.7%.In the multivariate analysis, maternal education level (OR=1.417; 95% CI) and knowing an affected patient (OR=4.215; 95% CI) were associated with a greater likelihood of being previously informed.Conclusions:Our study demonstrated that students had insufficient knowledge on hemoglobinopathies in a region where the disorders are prevalent. Organizing and sustaining educational activities related to hemoglobinopathies - particularly genetic basics of the disorders - to students, who are the parents of the future, may be useful in combating hemoglobinopathies. Keywords:Hemoglobinopathies, Awareness, School Health, Middle School Students, High School Students
Keywords: Hemoglobinopathies; Awareness; School Health; Middle School Students; High School Students